Contractor’s Selection Criteria in Construction Works in Pakistan - Soomro, N. U. I.; Memon, A. H.; Memon, N. A.; Memon, K. R. (Engineering, Technology & Applied Science Research, 2020)
The contractor is the primary stakeholder in materializing a project concept. For the successful completion of any project, it is compulsory for the contractor to have relevant experience. The selection of the appropriate contractor depends on various criteria. This study aims to study these selection criteria. Based on 71 questionnaire forms received from representatives of contractor, consultant and client firms involved in execution works of construction activities it is found that quality, bid amount, technical capability, financial stability, and experience are five commonly adopted criteria for contractor selection in construction works in Pakistan. On the other hand, quality, technical capability, financial stability, equipment availability, and management capability are reported as the top five effective criteria for appropriate contractor selection for any construction project.